Reimagining Teacher Administrative Management: Studi Kasus Implementasi Sistem Terpadu 360 Berbasis Google Sites Di MI Al Ikhlas Parakan Jawa Tengah - Yoga Prada; Muhammad Iqbal Birsyada (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of digital technology requires a transformation in teacher administration management that is more effective, efficient, and integrated, but in practice there are still many elementary schools that manage administration manually and separately so as to increase the workload of teachers. This study aims to analyze the implementation of the Google Sites-based TERPADU 360 System in improving the effectiveness of teacher administration management at MI Al Ikhlas Parakan, Central Java.This study employs a qualitative approach with a case study design involving 3 informants consisting of 1 head of madrasah and 2 classroom teachers selected through purposive sampling based on specific criteria, including direct involvement in administrative management, experience in using the system, and minimum one year of administrative experience. Data collection techniques were carried out through in-depth interviews, observations, and documentation. Data analysis was conducted using an interactive analysis model by Miles and Huberman, which includes data reduction, data display, and conclusion drawing, combined with data validation through triangulation of sources and techniques to ensure the credibility of findings. The results of the study show that the developed system is able to integrate all administrative components in one centralized platform, thereby improving time efficiency, ease of access, and data accuracy. In addition, the system has the characteristics of being simple, adaptive, and easy to use without requiring complex technical capabilities. The implementation of the system also has an impact on reducing the administrative burden of teachers so that they can increase the focus on learning activities. Thus, the Google Sites-based INTEGRATED 360 System has proven to be effective as an innovative model in the management of integrated and contextual teacher administration at the madrasah ibtidaiyah level.